Foreign Aid: Nigerian Legal and Economic Albatross - Obijiaku, I. O. (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The  Nigerian  economy  is stunted  in growth  with  its  attendant  poor  living standard  of   the people. Despite   the enormous  resources  and human  capital   at  her  disposal,  it  depends   on  foreign  aid to  execute its  capital  projects like  other developing nations. Regrettably, this foreign aid  is  mismanaged  and  in some  cases siphoned  into private foreign  accounts. This  articles   chronicles  the concept of  foreign aid, its  distribution and  international law  implications on the  sovereignty  of  the Nigerian State as well  as the  economic distress that comes in its  wake  among others.